PENGARUH SERAT BAMBU TERHADAP KAPASITAS LENTUR PELAT BETON CAMPURAN STYROFOAM DEGAN PERKUATAN TULANGAN WIREMESH - vega aditama; Ester Priskasari; Mohammad Erfan (Jurnal Teknik Sipil Info Manpro, 2024)
Lightweight concrete is a concrete technology innovation that is currently developing. The advantage of lightweight concrete is that it uses less time and costs compared to concrete in general but has the disadvantage of lower strength. This research aims to determine the effect of adding bamboo fiber on the flexural capacity of lightweight concrete slabs mixed with Styrofoam. The lightweight concrete mixture used is Styrofoam at 50% of the weight of the mixed aggregate. Variations in adding bamboo fiber with a diameter of 1 mm and a length of 40 mm are 0% and 0.5% of the cement weight. The test object consists of a lightweight concrete plate measuring 50 cm x 150 cm x 8 cm with wire mesh reinforcement with a diameter of 8 mm. Tests were carried out when the concrete was 28 days old by applying an even load gradually until the slab collapsed. From the test results, at a loading of 300 kg, the average deflection value for lightweight concrete slabs with reinforcement reinforcement with 0% bamboo fiber was 1.18 mm and for lightweight concrete slabs with 0.5% bamboo fiber was 1.57 mm. Lightweight concrete slabs mixed with bamboo fiber have a greater deflection than lightweight concrete slabs without a mix of bamboo fiber. This shows that the addition of bamboo fiber to lightweight concrete slabs does not increase the flexural capacity of the slab. The difference between theoretical calculations and testing is due to the theoretical calculation formula used in this research not taking into account the content and properties of Styrofoam in the plates. The two variations of concrete slabs used in the test did not experience any cracks and met the maximum allowable deflection requirements at loads reaching 300 kg.